Collective action for changing forests: A spatial, social-ecological approach to assessing participation in invasive plant management. (November 2021) - Sullivan, Abigail; York, Abigail M.
Highlights: Motivating collective action is important to address environmental change. We analyze the impact of space and time on collective invasive species management. Spatial patterns influence collective action with relevance to institutional design. Social and biophysical factors also influence collective action in different ways. Abstract: Environmental governance research has discovered much about what drives collective action to address human-environment issues, including factors such as risk perceptions and self-efficacy. Yet the design of many studies limits our ability to draw conclusions about collective action under conditions of environmental change, especially across spatial or temporal scales. In this study, we integrate social and biophysical data—assessing data over time and examining the influence of space—to analyze efforts by community members to manage rapid environmental change in the form of an invasive plant ( Mikania micrantha ) in community forests in Chitwan, Nepal. Invasive species are an increasingly complex ethical, cultural, and ecological issue that is becoming more pressing with global environmental and social changes. We combine household surveys, ecological surveys, and spatial data in Bayesian hierarchical linear models to explore changes in the drivers of collective action since initial household surveys in 2014. We find that risk perceptions, reliance on forest resources, perceptions of forest safety, and M. micrantha abundance were the most influential factors in our models. Additionally, our findings suggest that the influence of M. micrantha abundance on collective action varies across spatial scales, indicating important interactions between social and biophysical drivers of collective action. Ultimately, our results highlight the importance of considering social and biophysical factors across space and time to inform the design of institutions that will be effective in addressing collection action problems tied to environmental change.